Deep Learning Approach to Improve Student Learning Outcomes in Social Studies at Elementary School - Ferlin Mega Notanubun; Ode Abdurrachman; Leonid Ritiauw (ETDC: Indonesian Journal of Research and Educational Review, 2026)
Social Studies (IPS) learning in fifth graders of Elementary School Lumahlatal is still dominated by a teacher-centered paradigm that impacts low student learning outcomes, so a more active and student-centered alternative approach is needed. This study aims to determine the effectiveness of the implementation of the deep learning approach in improving social studies learning outcomes in fifth graders of Elementary School Lumahlatal. Using a quantitative method with a pre-experimental one-group pretest-posttest design, this study involved 21 students in the even semester of the 2025/2026 academic year as a sample. Data was collected through observation, documentation, and test instruments that had been tested for validity on 15 questions (rcount > 0.456) and had very high reliability (Cronbach's Alpha 0.976). Data analysis using the Shapiro-Wilk normality test showed a normal data distribution (sig. > 0.05). The results of the study showed a significant transformation in student learning completion from 28.60% in the pretest to 100% in the posttest, with an average score increasing from 61.35 to 84.5. An N-Gain score of 0.69 confirmed that this approach was effective in the "Moderate" category. This study proves that the integration of joyful, mindful, and meaningful learning components in deep learning can provide a significant positive impact on material mastery compared to conventional methods, while contributing to the transformation of the learning paradigm to a student-centered one.